Estrous characteristics and steroid concentrations in Aceh cows (Bos indicus) after estrus synchronization using prostaglandin F2a - HAFIZUDDIN HAFIZUDDIN; HUSNURRIZAL HUSNURRIZAL; CUT NILA THASMI; HERRIALFIAN HERRIALFIAN; NABILA LIONANDA SALSABIL; TONGKU NIZWAN SIREGAR; AMALIA SUTRIANA (Society for Indonesian Biodiversity, 2024)
Abstract. Hafizuddin, Husnurrizal, Thasmi CN, Herrialfian, Salsabil NL, Siregar TN, Sutriana A. 2024. Estrous characteristics and steroid concentrations in Aceh cows (Bos indicus) after estrus synchronization using prostaglandin F2a. Biodiversitas 25: 322-328. This study aims to determine the estrous characteristics and steroid concentrations during estrus in Aceh cattle after estrus synchronization using prostaglandin F2a. This study involved 9 Aceh cows with good reproductive status, not pregnant, and has shown at least 2 regular cycles, which were divided into 3 treatment groups. The first group (GI) received a single injection treatment, the second group (G2) received a double injection treatment with an interval of 10 days, and the third group (G3) was also treatment double injection with an interval of 12 days. Symptoms and responses to estrus were reported descriptively, and the data collected on onset, intensity, and duration of estrus were analyzed using one-way analysis of variance followed by Duncan's test. The results showed that estrus symptoms were almost similar and estrus response was 100% in all three treatment groups. The onset of estrus in G1, G2, and G3 did not differ significantly (P>0.05) with values of 68.00±18.33, 60.00±0.00, and 72.00±24.00 hours, respectively. The intensity of estrus in G1, G2, and G3 showed significant differences (P<0.05) with scores of 3.00±0.00, 5.00±0.00 and 4.33±1.15, respectively. The duration of estrus showed no significant difference in G1, G2, and G3 (P>0.05) with durations of 32.00±18.33, 72.00±0.00, and 52.00±38.57 hours, respectively. The concentrations of estradiol and progesterone obtained also showed no significant differences (P>0.05) in G1, G2, and G3, with respective concentrations of 91.67±24.77, 132.00±23.15, 89.47±24.19 pg/mL and 0.98±0.59, 0.86±0.18, 1.00±0.17 ng/mL. In conclusion, estrus synchronization with PGF2a single injection and double injection in Aceh cattle was found to have 100% estrus response. However, PGF2a with double injection showed higher estrus intensity compared to single injection. In Aceh cows, the recommended protocol for estrus synchronization using PGF2a is double injection.